A Percussão na Performance Musical do Grupo Capoeira Angola Comunidade. - Medeiros, Wenia Xavier de (2012)
This research, in the scope of ethnomusicology, was carried out towards musical performance, having as its object of study the Master Naldinho Capoeira Angola community group, located in the Novais district, in João Pessoa, Paraíba. The general objective of this research was to present, analyze and reflect about the fundamental aspects which characterize the Capoeira Angola Community Group musical performance giving emphasis to its musical practice and its bond to the various elements of the cultural universe, especially towards the role and the general characteristics when playing the percussion instruments in the performance context. The research was carried out under ethnographic methodology – essentially centered on qualitative research instruments of data collection– in order to accomplish the proposed aims. To gather data, it was used bibliographic research, semi- structured interviews and participative observation which enabled the researcher to make recordings on video and audio, as well as photographic ones. To organize, analyze, and read the data it was needed to elaborate theoretical framework, musical transcriptions, design interviews, select photographies, and describe the fundamental aspects of this cultural manifestation. As a result of these processes , it was presented contemporary conceptions which gave ground to this dissertation leading to the contextualization of capoeira in Brazil and its symbolic shifting from political crime to immaterial Brazilian cultural heritage, having as its forerunner Master Bimba (from Capoeira Regional) and Master Pastinha (from Capoeira Angola). The research contextualized the moment when capoeira gave its first steps in Paraíba through the Soteropolitano Zumbi Bahia until reaching Master Naldinho’s House of Capoeira Angola, created by Master Nô from Bahia. When forming the group, Master Naldinho, not only shaped it, but gave specific and hierarchic structures, creating and developing peculiar sequences with musical complementation for each graduation. It is presented the constituent elements of musical performance of the group then part of the musical content collected given emphasis to the repertoire. It is also defined the particularities of the percussion instruments used in the group within the historical, technical and functional aspects. To conclude, it is analyzed the rhythmic structures and the toques from Capoeira de Angola in both roda presentations and in shows with the Berimbaus Angola Community Orchestra. Capoeira Angola musical practice is essentially collective, with importa nt entertaining, socializing and social inclusiveness functions – it also involves the preservation and the maintenance of traditions. Capoeira Angola is imbued with values, codes and believes that have group performative meaning with its inseparable eleme nts, such as its sonorous result characterized by the inter-relation between them.